Navigating between Tea and Rubber in Xishuangbanna, China: When New Crops Fail and Old Ones Work - Slothuus, C.F.; Schmidt-Vogt, D.; Mertz, O. (MDPI, 2020)
Following the massive expansion of rubber plantations in China, considerable research has been conducted on the impact of these landscape changes. The general consensus is that there have been negative impacts on the environment and positive impacts on local economies. However, since rubber prices dropped after 2011, the economic benefit to the local people is challenged and the impact on the local people and communities remains unclear. Using a mix of qualitative and quantitative methods, this longitudinal study investigates how the drop in rubber prices has affected a local community and the local people in Manlin, Xishuangbanna, China. It investigates local coping strategies and the importance of alternative income sources and shows how differentiated access to alternative lands creates increased economic inequality within the village when prices fluctuate. Three general coping strategies were identified amongst local rubber farmers: doing business as usual, changing rubber management practices, and stopping- or decreasing tapping frequency. Differences in coping strategies are linked to factors including access to alternative income sources and rubber perceptions. Moreover, households with access to tea land were found to have experienced negligible impacts of decreasing rubber prices as income from tea has increased more than income from rubber has decreased, leading to increasing intra-village economic inequality. We conclude that while this is a clear case of how income diversification is important for reducing livelihood vulnerability, it also shows that the large focus on rubber farming has created benefits in terms of improved infrastructure and connectivity that has helped expand the market for tea as well.